The effectiveness of cassava leaf meal (Manihot esculenta Crantz) in feed with enzymes supplementation on Broiler digestive organs - Ririn Angriani; Widya Hermana; Muhammad Ridla (Faculty of Animal Science, Universitas Brawijaya, 2022)
This research aimed to evaluate the effect of cassava leaf meal with enzyme supplementation in feed on the digestive organs of the broiler. The research used a completely randomized factorial design on 48 Cobb-strain broilers distributed into two observation factors and four replications (consisting of 2 samples). The observation factor is factor 1 is the addition of cassava leaf meal (0%; 1.5%; and 3.0%), and the second factor is the addition of non-starch polysaccharides and protease enzymes with each dose of 250 g/ton feed (with and without enzymes). The variables analyzed were the relative weight of the digestive organs, the relative weight of the parts of the small intestine, and the relative length of the parts of the small intestine. The data obtained were analyzed by analysis of variance (ANOVA), and if the results indicated significantly different, then the posthoc test was conducted. The results showed that the addition of cassava leaf meal could increase the relative weight of the gizzard significantly (p<0.05). The addition of enzymes can significantly decrease the relative weight of the gizzard, small intestine, pancreas, ileum, and the relative length of the duodenum and ileum (p<0.05). The use of cassava leaf meal in the feed up to 3.0% does not interfere with digestive organs. There was no interaction between cassava leaf meal and enzymes on size response of digestibility broiler organ. The addition of enzymes can offset the detrimental effects caused by the use of cassava leaf meals in feed.